DESAIN KURIKULUM BAHASA INDONESIA DI PERGURUAN TINGGI BERBASIS OBE UNTUK MENINGKATKAN DAYA SAING LULUSAN - Everhard Markiano Solissa; Andi Muh suktomansyah; Ferdiawan; Singgih Prastawa; Ratna Susanti; Windy Wonmally (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
The design of the Indonesian language curriculum in higher education plays a crucial role in equipping graduates with the necessary skills to compete in the global job market. This study examines the development of an Outcome-Based Education (OBE) curriculum framework for Indonesian language courses in universities, focusing on enhancing graduates' competitiveness. The research employs a qualitative approach by analyzing curriculum structures, learning objectives, and competency mapping aligned with industry needs and international standards. The findings highlight that an OBE-based curriculum ensures students acquire practical language proficiency, critical thinking skills, and effective communication abilities. Moreover, integrating real-world applications and performance-based assessments strengthens students’ readiness for professional environments. The study emphasizes the importance of continuous curriculum evaluation and stakeholder collaboration in maintaining its relevance. Implementing an OBE-based Indonesian language curriculum is expected to bridge the gap between academic learning and workforce demands, thereby increasing graduates' employability and competitiveness.